Climate-smart agriculture measurement, reporting and verification in the United Republic of Tanzania - World Agroforestry Centre; Unique Forestry and Land Use (2019)
In the United Republic of Tanzania, CSA has rapidly become a key mechanism for addressing both climate change and food security. Since 2011 more than nine CSA-related policies, programmes and projects have been implemented by the government and develop- ment partners (figure 1 and table 1). Outcomes from CSA projects, however, have not yet been tracked or reported on. As a result, policy makers receive limited feedback on the effectiveness of these programmes; outcomes do not count toward national development and climate goals; and CSA is not explicitly integrated into budgetary processes.